Small-scale OrganoCat processing to screen rapeseed straw for efficient lignocellulose fractionation - Martinez Diaz, Jimena; Grande, Philipp Michael; Klose, Holger (Frontiers in Chemical Engineering, 2023)
Agricultural residues such as rapeseed straw can be a valuable source of cellulose, sugars, and aromatic molecules like lignin. Understanding its composition is crucial in order to develop suitable processing technology for the production of biofuel or biochemicals from rapeseed straw. Here, we developed a small-scale OrganoCat system to screen multiple technical conditions and different samples at higher throughput and utilize this system to analyze straw samples from a set of 14 genetically different Brassica lines on their processability. Correlation analysis was performed to investigate the effects of cell wall polymer features on rapeseed biomass disintegration. At comparably mild reaction conditions, the differences in recalcitrance towards OrganoCat fractionation within the set were especially associated with parameters such as pectic polysaccharide content, acetylation, and hemicellulose composition. These findings can subsequently be used to optimize and scale up the pretreatment and fractionation of lignocellulose derived from rapeseed straw.